Morphological and physiological behavior in soybean (Glycine max) genotypes to drought stress implemented at pre- and post-anthesis stages - Sepanlo, Nesa; Talebi, Reza; Rokhzadi, Asad; Mohammadi, Hayedeh (Acta Biologica Szegediensis, 2014)
In order to evaluate the morphological and physiological responses of soybean genotypes to water deficit, a field experiment with 3 different soybean genotypes at three different irrigation regimes was carried out. Plants were grown either under optimum condition (irrigated), drought stress implemented before the flowering (pre-anthesis) and pod-filling stage (post-anthesis). Seed yield and measured morphological characters, except for number of seeds per plant and seed protein content, decreased from normal irrigation regime to water deficit stress in both flowering and pod filling growing stages. Leaf relative water content (RWC) was significantly decreased in all genotypes by water deficit at both growing stages, as well as both stressed environments had progressive fall in chemical osmolytes and chlorophyll content. With the present results, it can be concluded that drought stress retards the growth and metabolic activity of soybean genotypes. These parameters showed considerable variability under drought stress at different growth stages in soybean.